Examining green production and its role within the competitive strategy of manufacturers - Tim Baines; Steve Brown; Ornella Benedettini; Peter Ball (Journal of Industrial Engineering and Management, 2012)
Purpose: This paper reviews current literature and contributes a set of findings that capture the current state-of-the-art of the topic of green production. Design/methodology/approach: A literature review to capture, classify and summarize the main body of knowledge on green production and, translate this into a form that is readily accessible to researchers and practitioners in the more mainstream operations management community. Findings: The existing knowledge base is somewhat fragmented. This is a relatively unexplored topic within mainstream operations management research and one which could provide rich opportunities for further exploration. Originality/value: This paper sets out to review current literature, from a more conventional production operations perspective, and contributes a set of findings that capture the current state-of-the-art of this topic.